Varroa treatment with bromfenvinphos markedly suppresses honeybee biochemical defence levels. Issue 1 (27th June 2016) - Strachecka, Aneta; Olszewski, Krzysztof; Paleolog, Jerzy
Abstract: We examined the influence of bromfenvinphos, a commonly used acaricide, on activities of many metabolic enzymes affecting the biochemical defences/physiology of the western honeybee, Apis mellifera L. (Hymenoptera: Apidae), as well as on some metabolic compound concentrations, percentage of global DNA methylation, and Nosema spp. infection levels. Bromfenvinphos‐treated workers had decreased haemolymph volumes and higher protein concentrations on their cuticle but lower protein concentrations in the haemolymph. They had higher global DNA methylation levels independent of the age‐related variants. Bromfenvinphos decreased the activities of antioxidant enzymes (SOD, GPx, CAT, GST), acidic, neutral, and alkaline protease inhibitors and enzymatic physiological markers (AST, ALT, ALP), and concentrations of urea, uric acid, creatinine, cholesterol, glucose, Mg 2+, and Ca 2+ in worker haemolymph, depending on the age of the bees. Protease activities were higher only in the haemolymph of young bromfenvinphos‐treated bees in comparison with untreated bees. This compound decreased the activities of alkaline proteases and neutral protease inhibitors on the cuticle. Unexpectedly, in the treated bees, the activities of acidic and neutral proteases, and acidic and alkaline protease inhibitors, were higher in the young bees and lower in the older workers in comparison to the untreated group. The bromfenvinphos‐treated workers were more heavily infested with Nosema spp. Thus, bromfenvinphos not only supressed many levels of biochemical defences, and therefore stress‐resistance‐related biochemical pathways but also visibly increased the Nosema spp. infection levels.